RELATIONSHIP BETWEEN PARENTS' KNOWLEDGE LEVEL OF CHILD PATIENTS WITH ACUTE RESPIRATORY TRACT INFECTION (ARI) AND ANTIBIOTIC USE BEHAVIOR AT TANJUNG BINTANG COMMUNITY HEALTH CENTER IN 2024: Relationship Between Parents Knowledge Level Of Child Patients With Acute Respiratory Infection (ARI) And Antibiotic Use Behavior At Tanjung Bintang Community Health Center In 2024 - Isbiyantoro, Isbiyantoro; Wahyuni, Novita Tri; Hijrah, Hijrah; Faliandra, Dinda Renanti (JFL : Jurnal Farmasi Lampung, 2025)
Infectious diseases are one of the most common public health problems, especially in developing countries. The causes include age, season, living conditions and existing health problems. One of the infectious diseases is Acute Respiratory Infection or better known as (ARI). Efforts to treat ARI caused by bacteria with the use of antibiotics. This study aims to determine the relationship between the level of knowledge of parents of pediatric patients with acute respiratory infections (ARI) and antibiotic use behavior at the Tanjung Bintang Health Center in 2024. This type of research uses quantitative analytical cross-sectional design, the sampling technique uses the accidental sampling method with a total of 80 respondents. Data analysis in this study used the chi-square test technique. The results of this study obtained the level of parental education of elementary school (52.2%), junior high school education (15.0%) high school-college education (32.5%). Respondents with work as many as (75.5%) and unemployed as many as (25.5%), children aged 5-8 years (61.3%), aged 9-12 years (38.8%), male gender (52.5%) and female (47.5%) and mild ISPA (31.3%), moderate ISPA (63.8) and severe ISPA (5.0%), respondent knowledge level of knowledge level less (26.3%) and good knowledge level (73.8%), parental behavior less (26.3%) and good behavior (73.8%). Based on the chi-square test there is a significant relationship between the level of knowledge and parental behavior towards the use.   Keywords : Antibiotics, Behavior, ISPA, Knowledge